DETERMINATION OF METAL DEPOSITION AND ITS EFFECTS ON MINERAL NUTRIENT UPTAKE STATUS OF Pinus brutia Ten. FOR ASSESSMENT OF POLLUTION IMPACT IN ITS HABITAT-ISTANBUL - (:unkn) unknown (GLOBAL NEST, SECRETARIAT, 2013)
Pinus brutia Ten. (Turkish red pine) is a widespread evergreen tree in the Mediterranean and Aegean regions of Turkey. In this study, leaf (washed and unwashed) and bark samples of Turkish red pine and its co-located soil samples were examined for the assessment of the impact of heavy metal pollution on mineral nutrient status of the plant. The samples were collected from 5 different localities; 4 from the Bosporus region and one from Prince Island (control) in 2012 vegetation period. The standard procedures were used and the determinations of heavy metals and nutrient elements (Al, B, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb and Zn) in all samples were done using Inductively Coupled Plasma Optic Emission Spectroscopy (ICP-OES). Additionally, PM2.5 and PM10 profiles of the study area were investigated. According to our measurements, the lowest and highest heavy metal accumulations and the amount of mineral nutrients (mg/kg d. wt) were varied between 28.420-115.809 and 4191.285-5776.910 for Al, 1.308-11.432 and 9.318-15.803 for B, 1604.497-9312.622 and 2457.361-4817.899 for Ca, 0.307-1.587 and 0.803-1.890 for Cd, 0.064-0.579 and 3.860-6.731 for Co, 0.853-5.445 and 12.472-22.761 for Cr, 2.063-11.292 and 8.304-24.193 for Cu, 158.090-242.056 and 4733.993-5727.813 for Fe, 88.021-4312.240 and 1231.649-1931.372 for K, 98.325-850.764 and 2668.299-4489.028 for Mg, 3.752-9.764 and 143.698-278.108 for Mn, 45.716-1315.764 and 91.225-116.795 for Na, 0.889-7.746 and 7.437-15.750 for Ni, 3.917-14.341 and 31.122-71.762 for Pb and 10.268-35.844 and 43.746-122.258 for Zn in the plant parts and soil samples, respectively. The mass concentrations of fine (PM2.5) and coarse (PM10) mode aerosols varied from 11 to 27 and 37 to 68 mu g/m(3) at study area, respectively. The data revealed that P. brutia is capable of accumulating considerable amounts of metals and mineral nutrient uptake pattern was not altered extensively because of metal deposition in the plant showing relatively less contamination risk in the area. Finally, it was proven that P. brutia is a suitable organism to be used as a biomonitoring tool for conducting research on heavy metal pollution.
Keywords: Pinus brutia Ten.; Turkish Red Pine; Metal Pollution; Mineral Nutrient Uptake; Particulate Matter (PM); Turkey; PLAYGROUNDS; BIOMONITOR; CHROMIUM; PLANTS; ACCUMULATION; HEALTH; GROWTH; ZN; CD